Strawberry Hill - Anderson, Catherine (Adeline Catherine) (New York : Berkley, 2018)
As a camp cook, Vickie Brown loves feeding any size crowd in the great outdoors--with one notable exception. She never would have predicted shed join the crew led by gruff cowboy Slade Wilder, the man who broke her heart just days before their wedding. Life has gone on since Vickie left him, but Slade can admit his attraction to the one woman hes ever loved remains stronger than ever. If he wasnt in such desperate need of an experienced cook for his paying guests, he would send Vickie packing. He knows better than to seek out the company of the woman who broke off their engagement so many years ago. Except theres no escaping each other in the confines of the wilderness area, especially once their anger begins to soften in the shared close quarters. But after Vickie finds the courage to confront Slade, it will take a leap of faith for them to put their past behind him, even if its the only way to recapture their once-in-a-lifetime love.
Keywords: Mystic Creek (Or. : Imaginary place) -- Fiction; Romance fiction